Editorial: recognising the efficacy of licensed drug therapies for irritable bowel syndrome on bloating—a step in the right direction for targeted treatment? Authors' reply. Issue 2 (25th June 2021) - Nelson, Alfred D.; Black, Christopher J.; Houghton, Lesley A.; Lugo‐Fagundo, Nahyr Sofía; Lacy, Brian E.; Ford, Alexander C.
LINKED CONTENT: This article is linked to Nelson et al and Vasant papers. To view these articles, visit https://doi.org/10.1111/apt.16437 and https://doi.org/10.1111/apt.16440